Effects of square electric field pulses with random fluctuation on state dynamics of InAs/GaAs double quantum dots - A. Kesorn (2018)
© 2016 Taylor & Francis Group, LLC. The study investigated the influence of square electric-field pulses with random fluctuation on the state dynamics of InAs/GaAs double quantum dots (DQDs) charge qubits. The DQDs were proposed as a charge qubit under operation by a finite number of sequent square pulses of electric field, whose amplitude varied from −0.3 to 0.3 [mV/A°] with random fluctuation at various frequencies. Moreover, for a fixed period of a single pulse, the operation time can also have fluctuation. The state dynamics were analyzed by modelling the DQDs as a two-level quantum system with the effective Hamiltonian and solving the time-dependent Schrödinger equation with the fourth-order Runge-Kutta method using modelling parameters obtained by interpolating results from the tight-binding calculation. Without fluctuation, the state dynamics depicted on the Bloch sphere showed that the states can have different phases, while the probability profiles remain roughly the same with varying electric field strength. When the square pulses were added with uniform random fluctuations in amplitude of the electric field, it was found that the mean state dynamics remained close to that without fluctuation, and the standard deviation of the occupancy probability profiles was proportional to that of the random fluctuation. For fluctuations in operation time, such proportionality does not exist, and the effects on the standard deviation were more pronounced. By comparing the occupancy probability profiles with that without fluctuation, the accuracy of the averaged probability profiles is not monotonic, depending on the fluctuation strength, but there exist some moments in operation time when the profiles are close to the mean dynamics, for both types of fluctuations.